Competence of Islamic Religious Education Teachers in Implementation of Learning Media Based Information Communication Technology (ICT) To Mas Nurul Ulum - Israyani, Israyani; Ibrahim, Basri; Abidin, Zainal (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Study This aim for (1) For increase Islamic Education teacher competency in implementation of learning media ICT based at MAS Nurul Ulum, (2) For explain Teachers' ability to implement ICT based learning media at MAS Nurul Ulum, (3) For find solution obstacle And Islamic Education teacher solutions in implementation of learning media ICT based at MAS Nurul Ulum. Study This use descriptive qualitative approach. Results study show that (1) Competence of Islamic Religious Education (PAI) Teachers in Implementation of Learning Media ICT based at MAS Nurul Ulum, that the PAI teacher has show competence strong professional And relevant with demands modern education based on technology. This is looks from ability they in Mastery Material Lessons, Determination Objective Learning, Use Method and Learning Media, Learning Process Management, Evaluation Results Learning, Development Professionalism Sustainable, and Integration Mark Religious . (2) PAI teacher's ability in implementation of learning media ICT based at MAS Nurul Ulum show significant progress. Teachers have capable master, design, develop, and implementing digital media effective, with impact positive to quality learning And teacher professionalism. Strengthening competence technical, media innovation, and improvement facility And training sustainable become key For maximize utilization of ICT so that the learning process the more interactive, interesting, and relevant with demands modern education as well as values Islam. (3) H obstacles And Islamic Education Teacher Solutions in Implementation of Learning Media ICT based at MAS Nurul Ulum show that teachers face three obstacle main, namely limitations means And infrastructure, differences ability technical teacher in use technology, as well as low readiness student in learning digital based. Solutions, utilizing offline media, using device personal, collaborative between teachers in media creation, as well as combine ICT methods with approach conventional.